TSCESDP The Strategy of Community Empowerment in Encouraging Sustainable Development Participation Based on Local Potential in Sukorejo Village: Strategi Pemberdayaan Masyarakat dalam Mendorong Partisipasi dalam Pembangunan Berkelanjutan Berbasis Potensi Lokal di Desa Sukorejo - Nisak, Choirun; Daryono, Daryono; Suchaina, Suchaina (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2025)
Sustainable Development at the Village level requires the active involvement of the community as a subject as well as the main actor of development. Sukorejo Village has a variety of local potential, both natural, social, cultural and economic resources which if managed optimally can be a force in improving the welfare of the community. However, the utilization of this potential will not run effectively without a community empowerment strategy that is able to encourage active and sustainable participation. This study aims to analyze community empowerment strategies in encouraging participation in sustainable development based on local potential in Sukorejo Village, Pohjentrek District, Pasuruan Regency. This research uses a qualitative (in-depth interviews with village officials, community leaders, and local business actors) approach with a case study method to obtain a comprehensive picture of the process, dynamics, and impacts of the community empowerment program implemented. Community empowerment in Sukorejo Village focuses on developing local potential in the fields of handicrafts, agriculture, and culture as the main driver of a sustainable creative economy. The strategy has been proven to be able to increase independence, active participation, and public awareness of the importance of development that is oriented towards a balance between economic, social, and environmental aspects. In relation to Sustainable Development, Sukorejo Village has shared local potential that supports the achievement of SGG 8 in local resource-based economic development, SDG 4 in strengthening community capacity.